2012
DOI: 10.1039/c2cc32839a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensing based on printable temporary transfer tattoos

Abstract: The realization of epidermal chemical sensing requires a fabrication methodology compatible with the non-planarity and irregularities of the human anatomy. This Communication describes the development of printed temporary transfer tattoo (T3) electrochemical sensors for physiological and security monitoring of chemical constituents leading towards the demonstration of ‘electronic skin’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 14 publications
0
120
0
2
Order By: Relevance
“…Currently, wearable sensors are mainly applied to the measurement of electrical activity produced by the brain and heart of humans noninvasively (342). Recently, Windmiller et al (344) showed that on-skin tattoo electrodes can be fabricated and employed for electroanalytical measurements, though no real-time body-sensing measurements were reported. The combination of tattoo-based electrochemical sensors with wearable electronics may, in the future, assist with the realization of fully functional electronic skin (344,345).…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, wearable sensors are mainly applied to the measurement of electrical activity produced by the brain and heart of humans noninvasively (342). Recently, Windmiller et al (344) showed that on-skin tattoo electrodes can be fabricated and employed for electroanalytical measurements, though no real-time body-sensing measurements were reported. The combination of tattoo-based electrochemical sensors with wearable electronics may, in the future, assist with the realization of fully functional electronic skin (344,345).…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
“…Recently, Windmiller et al (344) showed that on-skin tattoo electrodes can be fabricated and employed for electroanalytical measurements, though no real-time body-sensing measurements were reported. The combination of tattoo-based electrochemical sensors with wearable electronics may, in the future, assist with the realization of fully functional electronic skin (344,345). This is a most interesting and also challenging research subject, as, in principle, it may allow important parameters related to personal health to be continuously monitored in a noninvasive or minimally invasive manner (56).…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…From the fabrication standpoint, photolithography, screenprinting, and stamping methods are common approaches for the implementation of electrodes on planar substrates, which have also been used to realize functional sensing 'tattoos' on the body 2,5,31 . In these methods, the size of the electrodes depends on the feature size on the photo mask, stencil or shadow mask.…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente, estes estudos foram ampliados para o monitoramento de forma não invasiva dos eletrólitos e metabólitos na epiderme baseado em eletrodos flexíveis do tipo tatuagem temporárias que aderem à superfície da pele [60,64,65].…”
Section: Resultsunclassified